The future for wildlife on Kenya’s rangelands: an economic perspective - Norton-Griffiths, M.; Said, Mohammed Yahya (Wiley, 2010)
The briefing paper creates an awareness platform focusing on Kenya's rangelands that are undergoing a fundamental transformation in land use from nomadic, transhumant pastoralism to a more sedentary agro-pastoralism. Current conservation policy in Kenya, as evidenced by the new Wildlife Act (2007), demonstrates little awareness by the Government of Kenya of either the magnitude of these problems or of any real commitment to redress them. Over half of the most productive rangelands in Kenya, which used to hold the great majority of wildlife, are now supporting agricultural production with an associated rapid evolution of property rights from large land parcels under communal or group ownership to small land parcels under private ownership. This is attributed to the economic process of transformation that is cascading down the rainfall gradient and is proceeding faster, and is more advanced, in the areas of higher agricultural potential. This transformation is being driven by macro and micro economic forces within the Kenyan economy which scarcely existed even 25 years ago. At the macroeconomic scale both domestic (primarily urban) and international markets are expanding, there are real gains in producer prices, ever-increasing opportunities for off-farm jobs and investment, and a wider availability and choice of goods and services. At the micro-economic level are improved market and transport networks, improved information networks about market conditions, and improved access to financial services. All of these create incentives for pastoral landholders to increase returns to land by investing in land development and production. While livestock seem to be generally absorbed within the expanding agricultural and settlement frontier, wildlife are being displaced and eliminated.